Analysis of metabolites and metabolism-mediated biological activity assessment of ginsenosides on microfluidic co-culture system - Li, Zhongyu; Li, Jiwen; Sun, Mei; Men, Lei; Wang, Enhua; Zhao, Yiran; Li, Keke; Gong, Xiaojie (Frontiers in Pharmacology, 2023)
In vivo, the complex process of drugs metabolism alters the change in drug composition and determines the final pharmacological properties of oral drugs. Ginsenosides are primary constituents of ginseng, whose pharmacological activities are greatly affected by liver metabolism. However, the predictive power of existing in vitro models is poor due to their inability to mimic the complexity of drug metabolism in vivo. The advance of organs-on-chip-based microfluidics system could provide a new in vitro drug screening platform by recapitulating the metabolic process and pharmacological activity of natural product. In this study, an improved microfluidic device was employed to establish an in vitro co-culture model by culturing multiple cell types in compartmentalized microchambers. Different cell lines were seeded on the device to examine the metabolites of ginsenosides from the hepatocytes in top layer and its resulting efficacy on the tumors in bottom layer. Metabolism dependent drug efficacy of Capecitabine in this system demonstrated the model is validated and controllable. High concentrations of CK, Rh2 (S), and Rg3 (S) ginsenosides showed significant inhibitory effects on two types of tumor cells. In addition, apoptosis detection showed that Rg3 (S) through liver metabolism promoted early apoptosis of tumor cells and displayed better anticancer activity than prodrug. The detected ginsenoside metabolites indicated that some protopanaxadiol saponins were converted into other anticancer aglycones in varying degrees due to orderly de-sugar and oxidation. Ginsenosides exhibited different efficacy on target cells by impacting their viabilities, indicating hepatic metabolism plays an important role in determining ginsenosides efficacy. In conclusion, this microfluidic co-culture system is simple, scalable, and possibly widely applicable in evaluating anticancer activity and metabolism of drug during the early developmental phases of natural product.